2012
DOI: 10.1021/nl2036222
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Spectroscopy on an Individual Quantum Dot Using Atomic Force Microscopy

Abstract: We present a new charge sensing technique for the excited-state spectroscopy of individual quantum dots, which requires no patterned electrodes. An oscillating atomic force microscope cantilever is used as a movable charge sensor as well as gate to measure the single-electron tunneling between an individual self-assembled InAs quantum dot and back electrode. A set of cantilever dissipation versus bias voltage curves measured at different cantilever oscillation amplitudes forms a diagram analogous to the Coulom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…Electrons tunneling on and off the dot effectively damp the cantilever, and this damping exhibits Coulomb blockade peaks as a function of bias voltage similar to those well known in the dot conductance, even in the limit of weak coupling [8,9,10]. It has long been predicted that level degeneracy on the dot leads to lineshape asymmetry of Coulomb blockade peaks in the conductance [11].…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Electrons tunneling on and off the dot effectively damp the cantilever, and this damping exhibits Coulomb blockade peaks as a function of bias voltage similar to those well known in the dot conductance, even in the limit of weak coupling [8,9,10]. It has long been predicted that level degeneracy on the dot leads to lineshape asymmetry of Coulomb blockade peaks in the conductance [11].…”
mentioning
confidence: 58%
“…It has long been predicted that level degeneracy on the dot leads to lineshape asymmetry of Coulomb blockade peaks in the conductance [11]. Recently, we observed corresponding temperaturedependent peak shifts in the damping at weak coupling [10], but the lineshape asymmetry was far too small to be measured before now. However, by driving the cantilever to large oscillation amplitudes we enter a regime of strong coupling where its motion strongly modifies the tunneling rates on and off the dot, and leads to a dramatic enhancement of the lineshape asymmetry.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…The above described scheme was first developed and demonstrated for quantum dot systems, [57][58][59][60][61][62] and it was shown that even excited state properties can be extracted 63,64 -which provides a very exciting perspective also for molecular electronics. Later this scheme was applied also to the charging processes of single molecules.…”
Section: General Introductionmentioning
confidence: 99%
“…In frequency modulation 1 non contact atomic force microscopy (FM-NC-AFM), the cantilever oscillation amplitude is kept constant using an automatic gain controller, while the cantilever oscillation frequency keeps track of its resonance frequency. Variations in the energy required to maintain this constant amplitude are attributed to an energy transfer between tip and sample 2 and can be related to multiple physical effects such as electron tunneling, [3][4][5] Joule heating, 6 non-contact friction, 7 or atom rearrangements induced by short range interactions between tip and sample. [8][9][10] Despite extensive studies, quantitative dissipation measurements published generally show a large variation, in some cases not even agreeing on the relative magnitude.…”
mentioning
confidence: 99%